Problematika Pembelajaran TOAFL Pada Mahasiswa Fakultas Ilmu Tarbiyah dan Keguruan UIN Sulthan Thaha Saifuddin Jambi - Qodri, Muhammad (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2020)
This study aims to uncover the forms of TOAFL learning problems that occur in students of the Faculty of Tarbiyah and Teacher Training IAIN Sulthan Thaha Saifuddin Jambi, the causes and solutions to overcome these problems. This research is descriptive in nature using a qualitative approach. Data collection is done through interviews, observations, and documentation using snowball sampling techniques. The collected data are analyzed interactively through data reduction, data presentation, then drawing conclusions. Efforts to validate the data, researchers compared the observations with interviews and documentation, between the results of interviews with one informant with other informants with the same problem. The results of the study revealed that: 1) The form of TOAFL learning problems related to students is the difficulty in translating and understanding reading, poor vocabulary and weakness in mastering Arabic grammar. While the problems related to media and learning facilities are inadequate facilities and infrastructure, lack of use of learning media, minimal and difficulty in obtaining literature in the preparation of teaching materials to be presented. 2) The causes of TOAFL learning problems are: heterogeneous educational backgrounds of students, lack of interest and motivation to learn about TOAFL courses, low levels of student intelligence, and very little lecture time. 3) Efforts made to overcome these problems are by increasing motivation and interest in learning, giving attention and doing a lot of tamrinat (training), completing lecture facilities and facilities, utilizing existing lecture facilities and facilities, as well as getting around and increasing lecture time.